Comparison of speech intelligibility in a real and virtual living room using loudspeaker and headphone presentations - Schütze Julia; Kirsch Christoph; Kollmeier Birger; Ewert Stephan D. (Acta Acustica)
Virtual acoustics enables hearing research and audiology in ecologically relevant and realistic acoustic environments, while offering experimental control and reproducibility of classical psychoacoustics and speech intelligibility tests. Hereby, indoor environments are highly relevant, where listening and speech communication frequently involve multiple targets and interferers, as well as connected adjacent spaces that may create challenging acoustics. Hence, a controllable laboratory environment is evaluated here (by room acoustical parameters and speech intelligibility) which closely resembles a typical German living room with an adjacent kitchen. Target and interferer positions were permuted over four different locations, including an acoustically challenging position of a target in the kitchen with interrupted line of sight. Speech intelligibility was compared in the real room, in virtual acoustic representations, and in standard anechoic audiological configurations. Three presentation modes were tested: headphones, loudspeaker rendering on a small-scale, four-channel loudspeaker array in a sound-attenuated listening booth, and a three-dimensional 86-channel loudspeaker array in an anechoic chamber. The results showed that the target talker in the coupled room requires higher signal to noise ratios (SNRs) at threshold than typical indoor conditions. Moreover, for the stationary speech shaped interferer, effects of room acoustics were negligible. For a majority of target positions, no difference between the four-channel and the large-scale loudspeaker array were found, with an overall good agreement to the real room. This indicates that ecologically valid testing is feasible using a clinically applicable small-scale loudspeaker array.